Method of visualising relations between tweets to facilitate discussions via Twitter. (2017) - Yamada, Yasuhiro; Suzuki, Hiroshi; Hattori, Akira; Hayami, Haruo
It is common for Twitter users to adopt clients that display posts (tweets) as textboxes lined up in a perpendicular fashion. In a discussion with multiple participants, tweets are commonly used as 'replies'. However, it is difficult for users of these types of displays to follow the context and make further contributions to the conversations. In this study, we will also be proposing a system which visualises relations of tweets by usage of digraphs, along with an evaluation of the proposed system on how it fares with existing solutions.